The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3109/0886022x.2016.1143757
|View full text |Cite
|
Sign up to set email alerts
|

Ozone therapy ameliorates tubulointerstitial inflammation by regulating TLR4 in adenine-induced CKD rats

Abstract: Tubulointerstitium inflammation is a common pathway aggravating chronic kidney disease (CKD) progression and the mechanism is partly associated with excessive activation of toll-like receptor 4 (TLR4) in tubulointerstitium. Ozone therapy is demonstrated to alleviate inflammation in some experiments. The aim of this study is to examine whether ozone therapy could ameliorate chronic tubulointerstitium inflammation by suppressing TLR4 in adenine-induced CKD rats. SpragueDawley rats were fed with 0.75% adenine-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…TLR4, as the promoter of a signaling pathway, activates nuclear factor-κB (NF-κB) and stimulates pro-inflammatory responses. Some studies have revealed that the knockdown of the TLR4 significantly reduces the risk of fibrosis [37]. Renal fibrosis could be effectively ameliorated through inhibition of the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4, as the promoter of a signaling pathway, activates nuclear factor-κB (NF-κB) and stimulates pro-inflammatory responses. Some studies have revealed that the knockdown of the TLR4 significantly reduces the risk of fibrosis [37]. Renal fibrosis could be effectively ameliorated through inhibition of the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of NF-κB, a molecule involved in the TNFα/Tnfr1 cascade, by pyrrolidine dithiocarbamate also attenuated AdCKD progression 9 . Ozone therapy attenuated AdCKD by decreasing the expression of toll-like receptor 4 (TLR4) 10 , a lipopolysaccharide (LPS) receptor. Endoplasmic reticulum (ER) stress was also elevated in the kidneys of AdCKD mice, although this was reduced by the fatty acid receptor GPR40 agonist and aggravated in GPR40 knockout mice 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact mechanism of action of ozonated autohemotherapy is less well characterized, amelioration of inflammation and tissue damage could play critical roles. 9,10 Furthermore, ozonated autohemotherapy is not only a safe procedure without reperfusion damage but also a much more economical and practical treatment, and this may, thus, benefit the global COVID-19 patient population with refractory hypoxemia.…”
mentioning
confidence: 99%